2021
DOI: 10.1021/acs.iecr.1c01190
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Melt Strength and Processability of Polyolefins by Addition of a Functionalized Additive Designed via the TEMPO-Driven Thiol-ene Reaction

Abstract: Thiol-ene chemistry with TEMPO as an initiator has been utilized to synthesize a first-generation dendrimer having eight peripheral hydroxyl groups. Long chain branched impact copolymer polypropylene (ICP) and linear low-density polyethylene (LLDPE) were prepared by a postreactor modification process by a meltgrafting dendrimer onto a polyolefin chain using peroxide and maleic anhydride as a co-agent. Long chain branching in ICP controlled the chain scission initiated by peroxide by increasing entanglement, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…It is noteworthy to mention that in our previous work, we concluded that reactive extrusion with G1 enhanced processability while maintaining melt strength as that of neat ICP. [29] In the present work, we observed improved processability as well as melt strength as compared to neat ICP using extended long-chain branching obtained via melt grafting of G2. The prepared samples were also examined for their impact, flexural, and tensile strength, and it was observed that there is no degradation in the bulk mechanical properties of ICP after grafting G2 on polymer chains.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…It is noteworthy to mention that in our previous work, we concluded that reactive extrusion with G1 enhanced processability while maintaining melt strength as that of neat ICP. [29] In the present work, we observed improved processability as well as melt strength as compared to neat ICP using extended long-chain branching obtained via melt grafting of G2. The prepared samples were also examined for their impact, flexural, and tensile strength, and it was observed that there is no degradation in the bulk mechanical properties of ICP after grafting G2 on polymer chains.…”
Section: Introductionsupporting
confidence: 53%
“…Precursor generation 1 dendrimer (G1) was synthesized as reported in our previous work. [ 29 ] Carboxyethyl acrylate, free radical initiator Luperox‐101 (luperox), and sodium sulfate were purchased from Sigma Aldrich Chemicals. 1‐Ethyl‐3‐(3‐dimethyl aminopropyl) carbodiimide (EDC) and 4‐dimethyl aminopyridine (DMAP) were supplied from Spectrochem.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous modifications have been performed with PP, and the new properties achieved have been studied in detail and are well reported. [3][4][5] To improve the properties and to enhance the performance of PP in packaging applications, various fillers 6 and additives are utilized with PP. Resch et al 7 investigated the morphology of different types of PP cast films prepared using different formulations and processing conditions.…”
Section: Introductionmentioning
confidence: 99%